(untitled) (International Seven Journal of Health Research, 2024)
The aim was to analyze the role of stem cells in Diabetes Mellitus, adopting the humanized perspective of Kolcaba’s Comfort Theory. The methodology used a reflexive approach, reviewing literature on platforms such as Google Scholar and PubMed. The results highlighted the capacity of stem cells in tissue regeneration in DM1, offering a promising vision. The scientific evidence revealed the versatility of stem cells, not only in insulin replacement, but also in differentiation into various cell lineages, broadening the therapeutic spectrum. The discussion addressed challenges including heterogeneity in individual responses, optimization of cell differentiation and ethical issues. The Comfort Theory enriched the analysis by highlighting the importance of compassionate care, promoting humanized practices and considering emotional dimensions. In stem cell transplantation, attention to the patient’s emotional well-being, psychological support and effective communication were crucial. Methodological limitations were acknowledged, suggesting more in-depth approaches in future research, and practical implications were highlighted, proposing the integration of Comfort Theory into the therapeutic approach to optimize care for patients with Diabetes Mellitus.